Nutritional biochemistry of the vitamins - Bender, David A. (Cambridge University Press, 2003)
An authoritative and comprehensive review of our current knowledge of the vitamins, their metabolic functions and the scientific basis for setting recommended intakes for the prevention of deficiency and promotion of optimum health. This book will be a valuable reference for students and specialists alike in the field of nutritional biochemistry.